Gross and Histopathological Renal Findings in Medico-Legal Autopsies: A Cross-Sectional Study in Maharashtra - Jafar Isakhan Pathan; Jaya Bhaskar Baviskar; Momin Sayed Kashif (Perspectives In Medical Research)
Background: Medico-legal autopsies offer a unique opportunity to detect renal pathologies that may be incidental or contributory to sudden and unnatural deaths. This study aimed to correlate gross and histopathological renal alterations with causes of death in autopsy cases. Methods: A cross-sectional study was conducted on 150 medico-legal autopsies in Maharashtra between December 1995 and November 1997. Gross renal examination assessed size, weight, capsular features, cortical thickness, and surface morphology. Formalin-fixed, paraffin-embedded tissue sections were stained with hematoxylin and eosin, along with special stains where necessary. Renal compartments- glomeruli, tubules, interstitium, and vasculature—were systematically examined and correlated with macroscopic findings, age, and cause of death. Results: Gross renal abnormalities were noted in 66 cases (44%), with renal cysts (22%) and bilateral contracted kidneys (10.66%) being the most common. Histopathological lesions were identified in 94 cases (63%). Acute tubular necrosis (ATN) was most frequent (37.23%), particularly in younger individuals with thermal injuries. Chronic tubulo-interstitial nephritis (29.78%) was associated mainly with accidental deaths. Nephrosclerosis (19.14%) occurred predominantly in older individuals. Notably, 28 macroscopically normal kidneys exhibited significant microscopic lesions. Distinct findings such as medullary ATN and hemorrhagic necrosis were characteristic of snakebite fatalities. Conclusion: Histopathology revealed significant renal pathology undetectable on gross examination in medico-legal autopsies. The associations of ATN with burns and TIN with accidents suggest potential causal links warranting further study. Comprehensive renal assessment is crucial for elucidating the role of kidney pathology in mortality during forensic evaluations.